Conectado: O que a Internet fez com você e o que você pode fazer com ela - Baldessar, Maria José (Brazilian journalism research, 2008)
An interesting book, although simple and easy to read, is “Conectado: o que a Internet fez com você e o que você pode fazer com ela” (Connected: what the Internet did to you and what you can do with it), by historian Juliano Spyer, published by Jorge Zahar Editora at the end of 2007. In the preface by Caio Túlio Costa we find an account of the Web´s origins and how it was used by journalists and researchers. And these origins, in Túlio Caio´s case, go back to the year 1988.